Hexagonal ferrite magnetic powder for bonded magnets and its manufacturing method, and bonded magnets and its manufacturing method

By using a hexagonal ferrite magnetic powder with the chemical formula AFe n-x Mn x O 1.5n-0.5x+1, the coercive force of bonded magnets is increased without reducing the particle diameter, addressing the challenges of flowability and manufacturing complexity in existing technologies.

JP7660015B2Active Publication Date: 2025-04-10DOWA ELECTRONICS MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021060035
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-04-10
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Existing methods for increasing the coercive force of bonded magnets using hexagonal ferrite magnetic powder face challenges, as reducing particle diameter to achieve higher coercive force can hinder the flowability of the magnetic powder and kneaded materials, complicating the manufacturing process.

Method used

The development of a hexagonal ferrite magnetic powder with a chemical formula AFe n-x Mn x O 1.5n-0.5x+1, where n=10.0-12.0, x=0.054-0.200, and A is one or more selected from Sr, Ba, and Pb, which allows for an increase in coercive force without reducing the particle diameter, thereby maintaining the flowability of the magnetic powder and kneaded materials.

Benefits of technology

This approach effectively increases the coercive force of bonded magnets while preserving the particle diameter of the hexagonal ferrite magnetic powder, enhancing the manufacturing process by maintaining the flowability of the magnetic powder and kneaded materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660015000001
    Figure 0007660015000001
  • Figure 0007660015000002
    Figure 0007660015000002
  • Figure 0007660015000003
    Figure 0007660015000003
Patent Text Reader

Abstract

To provide hexagonal ferrite magnetic powder for a bonded magnet and a manufacturing method thereof, capable of increasing the coercive force of an obtained bonded magnet without increasing the particle size of hexagonal ferrite magnetic powder.SOLUTION: There is provided hexagonal ferrite magnetic powder for a bond magnet, which is represented by a chemical formula AFen-xMnxO1.5n-0.5x+1 (where, n=10.0-12.0, x=0.054-0.200, and A represents one or more selected from among Sr, Ba and Pb). A in the chemical formula is preferably Sr and Ba, and the hexagonal ferrite magnetic powder for a bond magnet preferably has an average particle size of 0.5 μm or more and 5.0 μm or less, and a compression density of 3.0 g / cm3 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hexagonal ferrite magnetic powder used in ferrite-based bonded magnets and a method for producing the same. [Background technology]

[0002] Conventionally, ferrite sintered magnets have been used as high-magnetic magnets such as those used in small motors for AV equipment, OA equipment, automotive electrical components, etc., and magnet rolls in copiers, etc. However, ferrite sintered magnets have problems such as being prone to chipping and requiring polishing, which reduces productivity, as well as the difficulty of processing them into complex shapes.

[0003] For this reason, in recent years, rare earth bonded magnets have been used as high-coercivity magnets for small motors used in AV equipment, office automation equipment, automotive electrical components, etc. However, rare earth magnets cost about 20 times as much as sintered ferrite magnets, and have the problem of being prone to rust, so it is desirable to use hexagonal ferrite bonded magnets instead of sintered ferrite magnets.

[0004] Examples of such hexagonal ferrite magnetic powders for bonded magnets that have been proposed include magnetic powders for bonded magnets having a 50% particle size of 1.2 to 3.0 μm and substantially no fine particles of 0.2 μm or less (see Patent Document 1), and ferrite magnetic powders for bonded magnets that contain alkaline earth metals as components, have a chlorine content of 0.05% by weight or less, and are fixed using a rubber-based resin as a binder (see Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2000-294417 A [Patent Document 2] JP 2004-265936 A Summary of the Invention [Problem to be solved by the invention]

[0006] Conventionally, the method of adjusting the coercive force of a bonded magnet using hexagonal ferrite magnetic powder has mainly been to adjust the particle size of the hexagonal ferrite magnetic powder. The smaller the particle size of the hexagonal ferrite magnetic powder, the higher the coercive force of the bonded magnet obtained, and the larger the particle size of the hexagonal ferrite magnetic powder, the lower the coercive force of the bonded magnet obtained. However, the particle size of the hexagonal ferrite magnetic powder has a large effect on the flowability of the magnetic powder as a powder and the flowability of the kneaded product, which is an intermediate product in the bonded magnet manufacturing process. If the particle size of the hexagonal ferrite magnetic powder becomes small, the magnetic powder itself and the kneaded product in the bonded magnet manufacturing process will not flow, which may have a negative effect on the manufacturing process. Therefore, if the coercive force of the bonded magnet can be increased without reducing the particle size of the hexagonal ferrite magnetic powder, it is desirable because it increases the degree of freedom in designing the handleability of the magnetic powder itself and the kneaded product during bonded magnet manufacturing.

[0007] The present application provides a hexagonal ferrite magnetic powder for bonded magnets that can increase the coercive force of the resulting bonded magnet without reducing the particle size of the hexagonal ferrite magnetic powder, a method for manufacturing the same, and a bonded magnet using the magnetic powder, and a method for manufacturing the same. [Means for solving the problem]

[0008] Conventionally, hematite (α-iron oxide) has been widely used as an Fe raw material for hexagonal ferrite magnetic powder for bonded magnets. Industrial hematite is produced as a by-product in the steel manufacturing process, and therefore contains impurities such as manganese and chromium. However, hematite with a high Mn content has been avoided as a raw material for hexagonal ferrite magnetic powder for bonded magnets in order to suppress the generation of a different phase of MnFe2O4, which has low coercive force, in the magnetic powder, and hematite with a low Mn content has been used. However, as a result of various studies, the inventors of the present invention have come to the conclusion that the coercive force of hexagonal ferrite magnetic powder for bonded magnets can be increased by actively adding a small amount of Mn to hematite, and have completed the present invention.

[0009] That is, the hexagonal ferrite magnetic powder for bonded magnets of the present invention has the chemical formula AFe n-x Mn x O 1.5n-0.5x+1 (wherein n=10.0 to 12.0, x=0.054 to 0.200, and A is one or more selected from Sr, Ba, and Pb). In the above chemical formula, A is preferably Sr and Ba, the average particle size is preferably 0.1 μm or more and 10 μm or less, and the compressed density is 2.7 g / cm 3 More preferably, it is equal to or greater than this.

[0010] Another aspect of the present invention is a bonded magnet comprising the hexagonal ferrite magnetic powder for bonded magnets of the present invention and a resin.

[0011] In yet another aspect, the present invention relates to a compound represented by the formula AFe n-x Mn x O 1.5n-0.5x+1(where n=10.0-12.0, x=0.054-0.200, and A is one or more selected from Sr, Ba, and Pb) and a flux to obtain a raw material mixture, a firing step of firing the obtained raw material mixture to obtain a fired product, and a grinding step of grinding the obtained fired product, in which hematite containing Mn is used as the Fe raw material and the Mn raw material in the raw material of the hexagonal ferrite magnetic powder. This manufacturing method may further include a step of annealing the ground powder obtained in the grinding step, and it is preferable to use one or more selected from barium chloride and bismuth oxide as the flux.

[0012] From yet another perspective, the present invention is a method for producing a bonded magnet, which uses hexagonal ferrite magnetic powder for bonded magnets obtained by the method for producing hexagonal ferrite magnetic powder for bonded magnets of the present invention. Effect of the Invention

[0013] When a bonded magnet is manufactured using the hexagonal ferrite magnetic powder for bonded magnets obtained by the manufacturing method of the hexagonal ferrite magnetic powder for bonded magnets of the present invention, the coercive force of the bonded magnet can be increased without reducing the particle size of the hexagonal ferrite magnetic powder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] (Hexagonal ferrite magnetic powder for bonded magnets) The subject of the present invention is a compound of the formula AFe 12 O 19 It is a hexagonal ferrite magnetic powder with a magnetoplumbite (M-type) crystal structure based on the following basic structure. In this chemical formula, A is one or more of the elements Sr, Ba, and Pb.

[0015] (composition) The hexagonal ferrite magnetic powder for bonded magnets of the present invention has the chemical formula AFe n-x Mn x O 1.5n-0.5x+1(where n=10.0 to 12.0, x=0.054 to 0.200, and A is one or more selected from Sr, Ba, and Pb), and Mn is included as an essential element. In the magnetic powder, Mn is Mn 2+ (Mn(II)), and the amount of oxygen in the chemical formula (1.5n-0.5x+1) represents A as a divalent metal element and Fe as Fe 3+ (Fe(III)), O to O 2- In the hexagonal ferrite magnetic powder for bonded magnets of the present invention, Mn is calculated as Mn 2+ (Mn(II)), but Mn 3+ (Mn(III)), Mn 4+ It is believed that hexagonal ferrite magnetic powders containing Mn that exists as a different valence, such as (Mn(IV)), can also be produced by adjusting the sintering temperature, sintering atmosphere, etc., in the sintering step described below. The magnetic powders obtained in this way may also have the same effects as the present invention, provided that the molar ratios of A, Fe, and Mn are in the same ranges as those in the above chemical formula.

[0016] In order to obtain an effect of improving the coercive force when used in a bonded magnet, x, which is an index of Mn content, is set to 0.054 or more and 0.200 or less, preferably 0.065 or more and 0.180 or less, and more preferably 0.072 or more and 0.150 or less. If x<0.054, the effect of improving the coercive force of the bonded magnet will be limited, and if x>0.200, the coercive force of the bonded magnet will be lower than when x<0.054, so neither is preferable.

[0017] The value of n, which is mainly an index of the Fe content, is set to 10.0 or more and 12.0 or less in order to obtain a single phase of magnetoplumbite crystals. If the value is outside the upper or lower limit, a different phase other than magnetoplumbite crystals may be generated, which is not preferable.

[0018] The mechanism by which the inclusion of trace amounts of Mn in the hexagonal ferrite magnetic powder for bonded magnets of the present invention results in improved coercivity in the bonded magnet is not clear, but the inventors surmise that the substitution of trace amounts of Mn for the Fe sites of the ferrite crystals somehow makes it more difficult for domain walls to move in the ferrite crystals of the bonded magnet when the magnetic field is reversed, leading to improved coercivity.

[0019] As the element A in the chemical formula of the hexagonal ferrite magnetic powder for bonded magnets of the present invention, from the viewpoint of reducing the specific gravity of the resulting magnetic powder and making the bonded magnet lighter, it is preferable to use one or more selected from Sr and Ba. Also, from the viewpoint of improving the magnetic properties, it is more preferable to use Sr and Ba as the element A, and it is even more preferable to set the Sr / (Sr+Ba) molar ratio to 0.80 or more and 0.98 or less.

[0020] (Average particle size) The average particle diameter of the hexagonal ferrite magnetic powder for bonded magnets of the present invention, as determined by an air infiltration method (sometimes simply referred to as "average particle diameter" in this specification), is preferably 0.1 μm or more and 10 μm or less, and more preferably 0.5 μm or more and 5.0 μm or less, from the standpoint of obtaining a desirable coercive force for a magnetic powder for bonded magnets.

[0021] (Compressed density) The compressed density of the hexagonal ferrite magnetic powder for bonded magnets of the present invention is 2.7 g / cm from the viewpoint of enhancing the packing property of the magnetic powder. 3 It is preferable that the density is 2.8 g / cm or more. 3 More preferably, it is 3.0 g / cm or more. 3 The upper limit of the compressed density of the magnetic powder is not particularly specified, but it is preferably 3.8 g / cm. 3 It may be controlled to less than 3.5g / cm 3 It may be managed as follows:

[0022] (specific surface area) The specific surface area of ​​the hexagonal ferrite magnetic powder for bonded magnets of the present invention is 0.5 m 2 / g or more 8.0m2 It is preferable that the molecular weight is 1 / g or less.

[0023] (Magnetic properties of powder compacts) The hexagonal ferrite magnetic powder for bonded magnets of the present invention has a density of 2 tons / cm 2 Regarding the magnetic properties of the green compact obtained by compression molding at a pressure of 1000 MPa, it is preferable that the residual magnetic flux density Br is 1850 G or more.

[0024] (Powder magnetic properties) Regarding the powder magnetic properties of the hexagonal ferrite magnetic powder for bonded magnets of the present invention, the saturation magnetization σs is preferably 55 emu / g or more, and the coercive force iHc is preferably 3700 Oe or more and 5000 Oe or less.

[0025] (particle size distribution) Regarding the particle size distribution of the hexagonal ferrite magnetic powder for bonded magnets of the present invention, the volume-based cumulative 16% particle diameter (D16) measured by a laser diffraction particle size distribution analyzer is preferably 0.3 μm or more and 1.5 μm or less, the volume-based cumulative 50% particle diameter (D50) measured by a laser diffraction particle size distribution analyzer is preferably 0.5 μm or more and 7.0 μm or less, and the volume-based cumulative 84% particle diameter (D84) measured by a laser diffraction particle size distribution analyzer is preferably 1.0 μm or more and 10 μm or less.

[0026] (Manufacturing method of hexagonal ferrite magnetic powder for bonded magnets) The method for producing the hexagonal ferrite magnetic powder for bonded magnets of the present invention is to use a compound represented by the chemical formula AFe n-x Mn x O 1.5n-0.5x+1 (where n=10.0-12.0, x=0.054-0.200, A is one or more selected from Sr, Ba, and Pb) with a flux to obtain a raw material mixture, a firing step of firing the obtained raw material mixture to obtain a fired product, and a grinding step of grinding the obtained fired product, characterized in that hematite containing Mn is used as the Fe raw material and Mn raw material in the raw material of the hexagonal ferrite magnetic powder. Each step will be described in detail below.

[0027] (Mixing process) Chemical formula AFe n-x Mn x O 1.5n-0.5x+1 (where n=10.0-12.0, x=0.054-0.200, A is one or more selected from Sr, Ba, and Pb) is mixed with a flux to obtain a raw material mixture. In order to obtain the effects of the present invention, it is essential to use hematite containing Mn as the Fe raw material and the Mn raw material in the raw material of the hexagonal ferrite magnetic powder. Here, hematite containing Mn means that Mn exists in the hematite crystal in a state where a part of the Fe site is replaced by the Mn element. As an example of hematite in which Mn exists in a state where a part of the Fe site is replaced by the Mn element, hematite derived from the steel manufacturing process can be mentioned. Conventionally, as the Fe raw material of the hexagonal ferrite magnetic powder, hematite with a low Mn content in the crystal has been used to suppress the generation of a different phase of MnFe2O4 with low coercivity in the magnetic powder, and it has been controlled so that the Mn content does not become high as in the above chemical formula. On the other hand, in the manufacturing method of the present invention, hematite with a high Mn content in the crystal is actively used as the Fe raw material, and the amount of Mn in the hematite is adjusted so that the composition of the finally obtained hexagonal ferrite magnetic powder for bonded magnets satisfies the above chemical formula. n-x Mn x O 1.5n-0.5x+1In order to achieve a composition range expressed by the formula (where n = 10.0 to 12.0, x = 0.054 to 0.200, and A is one or more selected from Sr, Ba, and Pb), it is preferable to adjust the amount of each raw material so that the molar ratio Mn / (Sr+Ba+Pb) of the total amount of metal element A contained in the raw material of metal element A (one or more selected from Sr, Ba, and Pb) and the flux to the amount of Mn contained in the hematite, which is the Fe raw material, is 0.048 to 0.180, and the molar ratio (Fe+Mn) / (Sr+Ba+Pb) of the total amount of metal element A contained in the raw material of metal element A and the flux to the total amount of Fe and Mn contained in the hematite is 8.5 to 11.2.

[0028] As the Mn-containing hematite used as a raw material, it is preferable to use hematite derived from the steel manufacturing process, and it is preferable to use hematite having a Mn / Fe molar ratio of 0.0047 or more and 0.020 or less.

[0029] As the raw material of the metal element A (Sr, Ba and Pb), carbonates, oxides and hydroxides can be used, with carbonates being particularly preferred.

[0030] The numerical ranges of x and n in the above chemical formula and the type of metal element A are as already described in the section on the composition of the hexagonal ferrite magnetic powder for bonded magnets.

[0031] As the flux, a known one can be used, but it is preferable to use one or more selected from barium chloride, strontium chloride, lead chloride and bismuth oxide, and it is more preferable to use one or more selected from barium chloride and bismuth oxide. When barium chloride is used as the flux, it is more preferable to add it in an amount of 0.3 to 8 mass% based on the total mass of the raw material and the flux, and when bismuth oxide is used, it is preferable to add it in an amount of 0.1 to 2.0 mass% based on the total mass of the raw material and the flux. Both barium chloride and bismuth oxide may be used as the flux.

[0032] In the mixing step, the powders serving as the raw material for the hexagonal ferrite powder may be mixed and then granulated, and the resulting granulated material may be subjected to the next step, that is, the firing step.

[0033] (Firing process) This is a process for obtaining a fired product by firing the raw material mixture obtained in the mixing process. The firing temperature is preferably 1000 to 1400°C, and the firing atmosphere is preferably an oxidizing atmosphere, more preferably an air atmosphere. As the firing furnace, a known heat treatment device such as a rotary kiln, a roller hearth furnace, or a batch-type box furnace can be used.

[0034] (Crushing process) This is a process for pulverizing the sintered product obtained in the sintering process to obtain hexagonal ferrite magnetic powder for bonded magnets. The pulverization can be carried out by a known method, and may be in the form of wet pulverization using an attritor or the like as a pulverizing device, or in the form of dry pulverization using a vibrating ball mill or the like as a pulverizing device, or both wet and dry pulverization may be carried out.

[0035] (Annealing process) The hexagonal ferrite magnetic powder for bonded magnets obtained in the pulverization process may be subjected to an annealing treatment under known conditions, for example, an annealing temperature of 900° C. to 1000° C., and an annealing atmosphere of air.

[0036] (Manufacturing method of bonded magnets) A bonded magnet with high coercive force iHc can be obtained by mixing the hexagonal ferrite magnetic powder for bonded magnets obtained by the manufacturing method of the hexagonal ferrite magnetic powder for bonded magnets of the present invention with resin, lubricant, etc., kneading, and then molding in a magnetic field. Here, when mixing the magnetic powder with the resin, additives such as a lubricant and a silane coupling agent may be further added and mixed as necessary.

[0037] (Composition analysis method) A composition analysis was carried out on the hexagonal ferrite magnetic powder for bonded magnets by calculating the amount of each element by the fundamental parameter method (FP method) using a fluorescent X-ray analyzer (ZSX100e manufactured by Rigaku Corporation). In this composition analysis, the hexagonal ferrite magnetic powder for bonded magnets was packed into a measurement cell and subjected to a 10 ton / cm 2 The specimen was molded by applying a pressure of 0.01 mm for 20 seconds, the measurement mode was EZ scan mode, the measurement diameter was 30 mm, the sample form was oxide, and the measurement time was the standard time. After qualitative analysis in a vacuum atmosphere, a quantitative analysis was performed on the detected constituent elements. Elements such as Bi, which was added as a flux, and Cr and Ni, which are thought to be derived from impurities in the raw materials, were also detected, but all were in trace amounts of 0.4 mass% or less in oxide equivalent. These trace elements of 0.4 mass% or less in oxide equivalent were considered impurities, and the chemical formula of the hexagonal ferrite magnetic powder for bonded magnets was determined to be AFe from the analysis values ​​of the main components Sr, Ba, Fe, and Mn. n-x Mn x O 1.5n-0.5x+1 Here, the total amount of Mn in the hexagonal ferrite magnetic powder for bonded magnets obtained in the examples described later was Mn. 2+ (Mn(II)), Mn is also used in the charge compensation calculation. 2+ (Mn(II)).

[0038] (X-ray diffraction measurement) Using a powder X-ray diffractometer (Miniflex600 manufactured by Rigaku Corporation), measurements were performed by powder X-ray diffraction (XRD) with a tube voltage of 40 kV, a tube current of 15 mA, a measurement range of 15° to 60°, a scan speed of 1° / min, and a scan width of 0.02°. As a result of XRD measurement of the hexagonal ferrite magnetic powders for bonded magnets obtained in the examples and comparative examples described below, it was confirmed that all the obtained magnetic powders had a magnetoplumbite-type ferrite crystal structure.

[0039] (Method of measuring average particle size and specific surface area) The average particle diameter (APD) of the hexagonal ferrite magnetic powder for bonded magnets was measured by the air permeation method using a specific surface area measurement device (SS-100 manufactured by Shimadzu Corporation). The specific surface area of ​​this hexagonal ferrite magnetic powder for bonded magnets was measured by the BET single point method using a specific surface area measurement device (Monosorb manufactured by Quantachrome Corporation).

[0040] (Method of measuring compressed density) 10g of hexagonal ferrite magnetic powder for bonded magnets was filled into a cylindrical mold with an inner diameter of 2.54cm, and then 1 ton / cm was applied. 2 The density of the hexagonal ferrite magnetic powder for bonded magnets when compressed at a pressure of 0.1 g / mol / L was measured, and this was taken as the compressed density (CD) of the hexagonal ferrite magnetic powder for bonded magnets.

[0041] (Magnetic property measurement of powder compacts) 8g of hexagonal ferrite magnetic powder for bonded magnets and 0.4cm of polyester resin (P-resin manufactured by Nihon Chikagakusha Co., Ltd.) 3 The mixture was kneaded in a mortar, and 7 g of the resulting mixture was filled into a mold having an inner diameter of 15 mm and subjected to a pressure of 2 ton / cm 2 The compact was compressed at a pressure of 1000 MPa for 60 seconds, and the resulting molded product was removed from the mold and dried at 150°C for 30 minutes to obtain a green compact. The magnetic properties of this green compact were measured using a BH tracer (TRF-5BH manufactured by Toei Kogyo Co., Ltd.) in a measuring magnetic field of 10 kOe to determine the coercive force bHc, coercive force iHc, and residual magnetic flux density Br of the green compact.

[0042] (Method of measuring powder magnetic properties) The powder magnetic properties of the hexagonal ferrite magnetic powder for bonded magnets were measured by packing 20 mg of the hexagonal ferrite magnetic powder for bonded magnets into a cell and then fixing it with molten paraffin. The saturation magnetization σs, residual magnetization σr, coercive force iHc, and reverse magnetization distribution SFD were measured at a magnetic field of 10 kOe using a vibrating sample magnetometer VSM (Toei Kogyo, VSM-P7).

[0043] (Method of measuring particle size distribution) The particle size distribution of the hexagonal ferrite magnetic powder for bonded magnets was measured using a laser diffraction particle size distribution measuring device (HELOS&RODOS) manufactured by SYMPATEC with a focal length of 20 mm, a dispersion pressure of 5.0 bar, and a suction pressure of 130 mbar, to determine the volume-based cumulative 16% particle size (D16), cumulative 50% particle size (D50), and cumulative 84% particle size (D84).

[0044] (Manufacturing test of mechanically oriented bonded magnets) 110 parts by mass of hexagonal ferrite magnetic powder for bonded magnets and 15 parts by mass of NBR rubber (N215SL manufactured by JSR Corporation) were kneaded for 10 minutes at 80°C using a lab blast mill (4C150 manufactured by Toyo Seiki Seisakusho Co., Ltd.), and the resulting kneaded material was rolled using a rolling machine (6B roll manufactured by Toyo Seiki Seisakusho Co., Ltd.) to produce a sheet with a thickness of 2.00 mm.

[0045] (Manufacturing test of magnetically aligned bonded magnets) 90.0 parts by mass of hexagonal ferrite magnetic powder for bonded magnets, 0.8 parts by mass of silane coupling agent (Z-6094N manufactured by Toray Dow Corning Co., Ltd.), 0.8 parts by mass of lubricant (VPN-212P manufactured by Henkel), and 8.4 parts by mass of powdered polyamide resin (P-1011F manufactured by Ube Industries, Ltd.) were weighed, charged into a mixer, and mixed. The mixture obtained was kneaded at 230°C using a lab blast mill (4C150 manufactured by Toyo Seiki Seisakusho Co., Ltd.) to obtain kneaded pellets with an average diameter of 2 mm. The kneaded pellets were loaded into an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd.) and molded at a temperature of 300°C and a molding pressure of 8.5 N / mm in a magnetic field of 9.7 kOe. 2 A cylindrical magnetically oriented bonded magnet with a diameter of 15 mm and a height of 8 mm was obtained by injection molding. Here, the magnetic field was oriented in a direction parallel to the central axis of the cylinder.

[0046] (Magnetic property measurement of bonded magnets) Using a BH tracer (TRF-5BH manufactured by Toei Kogyo Co., Ltd.), the coercive force iHc, residual magnetization Br and maximum energy product BHmax of the magnetically oriented bonded magnets and the mechanically oriented bonded magnets were measured in a measuring magnetic field of 10 kOe. EXAMPLES

[0047] Example 1 As a raw material for hexagonal ferrite magnetic powder for bonded magnets, it has a specific surface area of ​​5.8 m 2 / g strontium carbonate and a specific surface area of ​​4.9 m 2 Hematite (α iron oxide) containing manganese with a molar ratio of 0.0067 to Fe and a specific surface area of ​​0.2 m was prepared as a flux. 2 / g of barium chloride was prepared. Here, as hematite containing manganese, hematite crystals were prepared from a steel manufacturing process in which a part of the Fe site was replaced by Mn element (the same applies to the following examples and comparative examples). The prepared strontium carbonate, hematite, bismuth oxide, and barium chloride were weighed out so that the molar ratio of Sr:Fe:Mn=8.23:91.16:0.61 and the mass ratio of barium chloride in the mixture was 2.8 mass%, and mixed with a vibration mill to obtain a mixture. Here, the molar ratio Mn / (Sr+Ba+Pb) of the total amount of metal element A contained in the raw material of metal element A (one or more selected from Sr, Ba, and Pb) to the amount of Mn contained in hematite was 0.065, and the molar ratio (Fe+Mn) / (Sr+Ba+Pb) of the total amount of metal element A contained in the raw material of metal element A to the total amount of Fe and Mn contained in hematite was 9.75. The mixture was granulated in a pan pelletizer while adding 10% by weight of water based on the raw material, and the resulting spherical granules with a diameter of 3 to 10 nm were placed in an internal combustion rotary kiln and fired in an air atmosphere at 1150°C for 1 hour to obtain a fired product. 100 parts by mass of this fired product and 150 parts by mass of water were placed in an attritor and crushed for 90 minutes using a steel ball with a diameter of 5.56 mm as a medium to obtain a slurry. The solid obtained by filtering this slurry was dried in air at 300°C for 12 hours to obtain a dried cake. The dried cake was crushed in a mixer (SK-M10, manufactured by Kyoritsu Riko Co., Ltd.) and the resulting crushed product was annealed in air at 950°C for 30 minutes in an electric furnace to obtain a hexagonal ferrite magnetic powder for bonded magnets. The raw materials and manufacturing method described above are shown in Table 1 (the same applies to Examples 2 to 4 and Comparative Example 1).

[0048] When the obtained hexagonal ferrite magnetic powder for bonded magnets was subjected to XRD measurement, it was confirmed that the magnetic powder was a single phase of magnetoplumbite type crystals (the same applies to the following Examples and Comparative Examples). In addition, a composition analysis was performed on the obtained hexagonal ferrite magnetic powder for bonded magnets, and the average particle size, specific surface area, compressed density, magnetic properties of the green compact, magnetic properties of the powder, and particle size distribution were measured (the same applies to the following Examples and Comparative Examples). In addition, a manufacturing test of a mechanically oriented bonded magnet was performed using the obtained hexagonal ferrite magnetic powder for bonded magnets, and the magnetic properties of the bonded magnet obtained were measured (the same applies to Examples 2 to 4 and Comparative Example 1). The above measurement results are shown in Tables 2 and 3 (the same applies to Examples 2 to 4 and Comparative Example 1).

[0049] As a result of the above measurements, the obtained hexagonal ferrite magnetic powder for bonded magnets was found to have the chemical formula AFe n-x Mn x O 1.5n-0.5x+1 In this case, n was 10.8, x was 0.079, and the Sr / (Sr+Ba) molar ratio was 0.87. The average particle size of the obtained hexagonal ferrite magnetic powder for bonded magnets was 0.99 μm, and the compressed density was 3.10 g / cm. 3 and the specific surface area is 2.59m 2 / g. The iHc of the resulting bonded magnet was 3763 Oe.

[0050] Example 2 Hexagonal ferrite magnetic powder for bonded magnets was obtained using the same procedure as in Example 1, except that hematite (α-iron oxide) containing manganese in a molar ratio to Fe of 0.0064 was used, and strontium carbonate and hematite were weighed out so that the molar ratio of Sr:Fe:Mn was 8.23:91.19:0.58. The obtained hexagonal ferrite magnetic powder for bonded magnets is n-x Mn x O 1.5n-0.5x+1In this case, n was 10.9, x was 0.069, and the Sr / (Sr+Ba) molar ratio was 0.87. The average particle size of the obtained hexagonal ferrite magnetic powder for bonded magnets was 0.97 μm, and the compressed density was 3.10 g / cm. 3 and the specific surface area is 2.48m 2 / g. The iHc of the resulting bonded magnet was 3645 Oe.

[0051] Example 3 Hexagonal ferrite magnetic powder for bonded magnets was obtained using the same procedure as in Example 1, except that hematite (α-iron oxide) containing manganese at a molar ratio of 0.0055 to Fe was used, and strontium carbonate and hematite were weighed out so that the molar ratio of Sr:Fe:Mn was 8.23:91.27:0.50. The obtained hexagonal ferrite magnetic powder for bonded magnets is n-x Mn x O 1.5n-0.5x+1 In this case, n was 10.8, x was 0.062, and the Sr / (Sr+Ba) molar ratio was 0.88. The average particle size of the obtained hexagonal ferrite magnetic powder for bonded magnets was 1.02 μm, and the compressed density was 3.13 g / cm. 3 and the specific surface area is 2.43 m 2 / g. The iHc of the resulting bonded magnet was 3640 Oe.

[0052] Example 4 Hexagonal ferrite magnetic powder for bonded magnets was obtained using the same procedure as in Example 1, except that hematite (α-iron oxide) containing 0.0049 manganese to Fe molar ratio was used, and strontium carbonate and hematite were weighed out so that the molar ratio of Sr:Fe:Mn was 8.23:91.31:0.45. The obtained hexagonal ferrite magnetic powder for bonded magnets is n-x Mn x O 1.5n-0.5x+1In this case, n was 11.0, x was 0.055, and the Sr / (Sr+Ba) molar ratio was 0.87. The average particle size of the obtained hexagonal ferrite magnetic powder for bonded magnets was 0.99 μm, and the compressed density was 3.12 g / cm 3 and the specific surface area is 2.47m 2 / g. The iHc of the resulting bonded magnet was 3599 Oe.

[0053] Comparative Example 1 Hexagonal ferrite magnetic powder for bonded magnets was obtained using the same procedure as in Example 1, except that hematite (α-iron oxide) containing manganese in a molar ratio to Fe of 0.0046 was used, and strontium carbonate and hematite were weighed out so that the molar ratio of Sr:Fe:Mn was 8.23:91.35:0.42. The obtained hexagonal ferrite magnetic powder for bonded magnets is n-x Mn x O 1.5n-0.5x+1 In this case, n was 10.8, x was 0.052, and the Sr / (Sr+Ba) molar ratio was 0.87. The average particle size of the obtained hexagonal ferrite magnetic powder for bonded magnets was 0.98 μm, and the compressed density was 3.09 g / cm. 3 and the specific surface area is 2.52 m 2 / g. The iHc of the resulting bonded magnet was 3537 Oe.

[0054] From the results of Examples 1 to 4 and Comparative Example 1, the chemical formula AFe n-x Mn x O 1.5n-0.5x+1 (where n=10.0-12.0, x=0.054-0.200, and A is one or more selected from Sr, Ba, and Pb) to obtain a hexagonal ferrite magnetic powder composition represented by the chemical formula AFe n-x Mn x O 1.5n-0.5x+1(where n = 10.0 to 12.0, x = 0.054 to 0.200, and A is one or more selected from Sr, Ba and Pb), it is possible to increase the coercive force of a bonded magnet obtained using this hexagonal ferrite magnetic powder without reducing the particle size of the hexagonal ferrite magnetic powder, and it is found that the larger the value of x (the higher the Mn content), the greater the effect of improving the coercive force.

[0055] Example 5 As a raw material for hexagonal ferrite magnetic powder for bonded magnets, it has a specific surface area of ​​5.8 m 2 / g strontium carbonate and a specific surface area of ​​4.9 m 2 Hematite (α iron oxide) containing manganese with a molar ratio of 0.0079 to Fe and a specific surface area of ​​2.3 m was prepared as a flux. 2 / g of bismuth(III) oxide and a specific surface area of ​​0.2 m 2 / g of barium chloride was prepared. The prepared strontium carbonate, hematite, bismuth oxide, and barium chloride were weighed out so that the molar ratio of Sr:Fe:Mn=8.26:91.01:0.72, and the mass ratios of bismuth oxide and barium chloride in the mixture were 0.33 mass% and 1.9 mass%, respectively, and mixed using a vibration mill to obtain a mixture. Here, the molar ratio Mn / (Sr+Ba+Pb) of the total amount of metal element A contained in the raw material of metal element A (one or more selected from Sr, Ba, and Pb) to the amount of Mn contained in hematite was 0.080, and the molar ratio (Fe+Mn) / (Sr+Ba+Pb) of the total amount of metal element A contained in the raw material of metal element A to the total amount of Fe and Mn contained in hematite was 10.12. The mixture was granulated in a pan pelletizer while adding 10% by mass of water based on the raw materials, and the resulting spherical granules with a diameter of 3 to 10 nm were placed in an internal combustion rotary kiln and fired in an air atmosphere at 1270°C (firing temperature) for 1 hour to obtain a fired product. 100 parts by mass of this fired product and 150 parts by mass of water were placed in an attritor and crushed for 90 minutes using a steel ball with a diameter of 5.56 mm as a medium to obtain a slurry. The solid obtained by filtering this slurry was dried in the air at 300°C for 12 hours to obtain a dried cake. The dried cake was crushed in a mixer (SK-M10, manufactured by Kyoritsu Riko Co., Ltd.) and the crushed product obtained was crushed for 14 minutes using a vibration ball mill (Uras Vibrator KEC-8-YH, manufactured by Murakami Seiki Kogyo Co., Ltd.) using a steel ball with a diameter of 12 mm as a medium at a rotation speed of 1800 rpm. The pulverized product thus obtained was annealed in an electric furnace in air at 950°C for 30 minutes to obtain a hexagonal ferrite magnetic powder for bonded magnets. The raw materials and manufacturing conditions described above are shown in Table 4 (the same applies to the following Examples and Comparative Examples).

[0056] The obtained hexagonal ferrite magnetic powder for bonded magnets was used to carry out a manufacturing test of a magnetically oriented bonded magnet, and the magnetic properties of the obtained bonded magnet were measured. The measurement results of the magnetic properties of the bonded magnet are shown in the table. In addition, the measurement results of each evaluation item of the ferrite magnetic powder for bonded magnets are shown in Tables 5 and 6 (the same applies to the following examples and comparative examples).

[0057] The obtained hexagonal ferrite magnetic powder for bonded magnets is n-x Mn x O 1.5n-0.5x+1 In this case, n was 11.5, x was 0.098, and the Sr / (Sr+Ba) molar ratio was 0.90. The average particle size of the obtained hexagonal ferrite magnetic powder for bonded magnets was 1.37 μm, and the compressed density was 3.33 g / cm 3 and the specific surface area is 1.70m 2 The iHc of the resulting bonded magnet was 3225 Oe.

[0058] Example 6 Hexagonal ferrite magnetic powder for bonded magnets was obtained by the same procedure as in Example 5, except that hematite (alpha iron oxide) containing 0.0063 manganese to Fe molar ratio was used, strontium carbonate and hematite were weighed out to give a molar ratio of Sr:Fe:Mn=8.27:91.17:0.57, and the sintering temperature was 1260°C. The obtained hexagonal ferrite magnetic powder for bonded magnets is n-x Mn x O 1.5n-0.5x+1 In this case, n was 10.9, x was 0.075, and the Sr / (Sr+Ba) molar ratio was 0.90. The average particle size of the obtained hexagonal ferrite magnetic powder for bonded magnets was 1.28 μm, and the compressed density was 3.34 g / cm 3 and the specific surface area is 1.78m 2 / g. The iHc of the resulting bonded magnet was 3023 Oe.

[0059] Comparative Example 2 Hexagonal ferrite magnetic powder for bonded magnets was obtained by the same procedure as in Example 5, except that hematite (α-iron oxide) containing 0.0043 manganese to Fe molar ratio was used, strontium carbonate and hematite were weighed out to give a molar ratio of Sr:Fe:Mn=8.27:91.34:0.39, and the sintering temperature was 1260°C. The obtained hexagonal ferrite magnetic powder for bonded magnets is n-x Mn x O 1.5n-0.5x+1 In this case, n was 11.1, x was 0.049, and the Sr / (Sr+Ba) molar ratio was 0.90. The average particle size of the obtained hexagonal ferrite magnetic powder for bonded magnets was 1.29 μm, and the compressed density was 3.36 g / cm. 3 and the specific surface area is 1.92 m 2 / g. The iHc of the resulting bonded magnet was 2957 Oe.

[0060] From the results of Examples 5 and 6 and Comparative Example 2, the chemical formula AFe n-x Mn x O 1.5n-0.5x+1 (where n = 10.0 to 12.0, x = 0.054 to 0.200, and A is one or more selected from Sr, Ba, and Pb) to obtain a hexagonal ferrite magnetic powder composition represented by the chemical formula AFe n-x Mn x O 1.5n-0.5x+1 (where n = 10.0 to 12.0, x = 0.054 to 0.200, and A is one or more selected from Sr, Ba and Pb), it is possible to increase the coercive force of a bonded magnet obtained using this hexagonal ferrite magnetic powder without reducing the particle size of the hexagonal ferrite magnetic powder, and it is found that the larger the value of x (the higher the Mn content), the greater the effect of improving the coercive force.

[0061] Example 7 Hexagonal ferrite magnetic powder for bonded magnets was obtained by the same procedure as in Example 5, except that hematite (α-iron oxide) containing manganese at a molar ratio of 0.0100 to Fe was used, strontium carbonate and hematite were weighed out to give a molar ratio of Sr:Fe:Mn=8.26:90.83:0.91, and the sintering temperature was 1295°C. The obtained hexagonal ferrite magnetic powder for bonded magnets is n-x Mn x O 1.5n-0.5x+1 In this case, n was 11.7, x was 0.127, and the Sr / (Sr+Ba) molar ratio was 0.91. The average particle size of the obtained hexagonal ferrite magnetic powder for bonded magnets was 1.44 μm, and the compressed density was 3.40 g / cm. 3 and the specific surface area is 1.67m 2 / g. The iHc of the resulting bonded magnet was 2,900 Oe.

[0062] Example 8 Hexagonal ferrite magnetic powder for bonded magnets was obtained by the same procedure as in Example 5, except that hematite (alpha iron oxide) containing manganese at a molar ratio of 0.0092 to Fe was used, strontium carbonate and hematite were weighed out to give a molar ratio of Sr:Fe:Mn=8.26:90.90:0.84, and the sintering temperature was 1290°C. The obtained hexagonal ferrite magnetic powder for bonded magnets is n-x Mn x O 1.5n-0.5x+1 In this case, n was 11.6, x was 0.121, and the Sr / (Sr+Ba) molar ratio was 0.90. The average particle size of the obtained hexagonal ferrite magnetic powder for bonded magnets was 1.42 μm, and the compressed density was 3.42 g / cm. 3 and the specific surface area is 1.74 m 2 / g. The iHc of the resulting bonded magnet was 2890 Oe.

[0063] Example 9 Hexagonal ferrite magnetic powder for bonded magnets was obtained by the same procedure as in Example 5, except that hematite (α-iron oxide) containing 0.0081 manganese to Fe molar ratio was used, strontium carbonate and hematite were weighed out to give a molar ratio of Sr:Fe:Mn=8.26:90.99:0.74, and the sintering temperature was 1285°C. The obtained hexagonal ferrite magnetic powder for bonded magnets is n-x Mn x O 1.5n-0.5x+1 In this case, n was 11.9, x was 0.107, and the Sr / (Sr+Ba) molar ratio was 0.90. The average particle size of the obtained hexagonal ferrite magnetic powder for bonded magnets was 1.39 μm, and the compressed density was 3.42 g / cm 3 and the specific surface area is 1.69m 2 / g. The iHc of the resulting bonded magnet was 2875 Oe.

[0064] Comparative Example 3 Hexagonal ferrite magnetic powder for bonded magnets was obtained by the same procedure as in Example 5, except that hematite (α-iron oxide) containing 0.0045 manganese to Fe molar ratio was used, strontium carbonate and hematite were weighed out to give a molar ratio of Sr:Fe:Mn=8.27:91.32:0.41, and the sintering temperature was 1300°C. The obtained hexagonal ferrite magnetic powder for bonded magnets is n-x Mn x O 1.5n-0.5x+1 In this case, n was 10.8, x was 0.050, and the Sr / (Sr+Ba) molar ratio was 0.90. The average particle size of the obtained hexagonal ferrite magnetic powder for bonded magnets was 1.46 μm, and the compressed density was 3.39 g / cm. 3 and the specific surface area is 1.60m 2 / g. The iHc of the resulting bonded magnet was 2852 Oe.

[0065] From the results of Examples 7 to 9 and Comparative Example 3, the chemical formula AFe n-x Mn x O1.5n-0.5x+1 (where n = 10.0 to 12.0, x = 0.054 to 0.200, and A is one or more selected from Sr, Ba, and Pb) to obtain a hexagonal ferrite magnetic powder composition represented by the chemical formula AFe n-x Mn x O 1.5n-0.5x+1 (where n = 10.0 to 12.0, x = 0.054 to 0.200, and A is one or more selected from Sr, Ba and Pb), it is possible to increase the coercive force of a bonded magnet obtained using this hexagonal ferrite magnetic powder without reducing the particle size of the hexagonal ferrite magnetic powder, and it is found that the larger the value of x (the higher the Mn content), the greater the effect of improving the coercive force.

[0066] [Table 1]

[0067] [Table 2]

[0068] [Table 3]

[0069] [Table 4]

[0070] [Table 5]

[0071] [Table 6]

Claims

1. Chemical formula AFe n-x Mn x O 1.5n-0.5x+1 (wherein n=10.0 to 12.0, x=0.062 to 0.200, and A is one or more selected from Sr, Ba, and Pb).

2. 2. The hexagonal ferrite magnetic powder for bonded magnets according to claim 1, wherein A in said chemical formula is Sr and Ba.

3. 3. The hexagonal ferrite magnetic powder for bonded magnets according to claim 1 or 2, having an average particle size of 0.1 μm or more and 10 μm or less.

4. Compressed density is 2.7 g / cm 3 The hexagonal ferrite magnetic powder for bonded magnets according to any one of claims 1 to 3.

5. A bonded magnet comprising the hexagonal ferrite magnetic powder for bonded magnets according to any one of claims 1 to 4 and a resin.

6. A method for producing a hexagonal ferrite magnetic powder for a bonded magnet, comprising the steps of: Chemical formula AFe n-x Mn x O 1.5n-0.5x+1 (where n=10.0 to 12.0, x=0.062 to 0.200, and A is one or more selected from Sr, Ba, and Pb) and a flux to obtain a raw material mixture; A firing step of firing the obtained raw material mixture to obtain a fired product; and a grinding step of grinding the obtained fired product, A method for producing hexagonal ferrite magnetic powder for bonded magnets, comprising using hematite containing Mn and having a Mn / Fe molar ratio of 0.0055 or more and 0.020 or less as the Fe raw material and the Mn raw material in the raw materials of the hexagonal ferrite magnetic powder.

7. The method for producing hexagonal ferrite magnetic powder for bonded magnets according to claim 6, further comprising a step of annealing the pulverized powder obtained in the pulverization step.

8. 8. The method for producing hexagonal ferrite magnetic powder for bonded magnets according to claim 6 or 7, wherein the flux is at least one selected from the group consisting of barium chloride and bismuth oxide.

9. A method for producing a bonded magnet, comprising using a hexagonal ferrite magnetic powder for a bonded magnet obtained by the method for producing a bonded magnet according to any one of claims 6 to 8.

Citation Information

Patent Citations

  • Ferrite powder for bonded magnets and method for producing same

    EP3696828A1

  • Preparation of iron oxide for raw material of ferrite from iron ore

    JP1987138332A

  • Method of producing magnetic powder for bonded magnet and bonded magnet

    JP2000294417A

  • Permanent magnet and manufacturing method for the same

    JP2001284113A

  • Strontium ferrite particles and powder for bonded magnet, and bonded magnet using the particles and power

    JP2002175907A